Digitalization and its Impact on the Future Role of SCM Executives in Talent Management – An International Cross-Industry Delphi Study - Manuel Wehrle; Sabrina Lechler; Heiko A. von der Gracht; Evi Hartmann (Journal of Business Logistics, 2021)
In the field of supply chain management (SCM), attracting and developing appropriate talent is critical for achieving most SCM goals, as extensive skills are necessary to do the job properly. In order to ensure that future-proof talent can continue to emerge in this discipline, the role of SCM executives is extremely important. Although many studies have been conducted in the field of talent management (TM), the future role of SCM executives has been mostly neglected in research. The present empirical study addresses this gap, taking into consideration the fourth industrial revolution, as innovation in technology continues to drive significant changes in the SCM field. Aiming to investigate the extent to which increasing digitalization is influencing the future role of SCM executives, a Delphi study with 103 experts from industry, academics, and politics/associations was carried out. In order to identify meaningful topic clusters from the data, fuzzy c-means clustering was used. From an actor-network theory perspective, our results show that in some areas of TM, digitalization is leading to a strong fusion of SCM executives and digital technologies, as well as to a clear division of roles, in which either SCM leaders or technology will dominate in the future.
Keywords: 650; talent management; digitalization; Delphi method; supply chain